2021
DOI: 10.1371/journal.pcbi.1009638
|View full text |Cite
|
Sign up to set email alerts
|

The impact of whole genome duplications on the human gene regulatory networks

Abstract: This work studies the effects of the two rounds of Whole Genome Duplication (WGD) at the origin of the vertebrate lineage on the architecture of the human gene regulatory networks. We integrate information on transcriptional regulation, miRNA regulation, and protein-protein interactions to comparatively analyse the role of WGD and Small Scale Duplications (SSD) in the structural properties of the resulting multilayer network. We show that complex network motifs, such as combinations of feed-forward loops and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 77 publications
5
28
0
Order By: Relevance
“…Investigation of three metazoan subbranches, pIrg1, Irg1L and Irg1, support the notion that genome duplication and gene loss provide a powerful evolutionary force to innovate gene expression regulatory mechanisms 72 . Our analysis is consistent with a second whole genome duplication in the vertebrate lineage (2R WGD) that produced the paralogs Irg1L and Irg1, in which Irg1L is subsequently lost in viviparous mammalian taxa.…”
Section: Discussionmentioning
confidence: 81%
“…Investigation of three metazoan subbranches, pIrg1, Irg1L and Irg1, support the notion that genome duplication and gene loss provide a powerful evolutionary force to innovate gene expression regulatory mechanisms 72 . Our analysis is consistent with a second whole genome duplication in the vertebrate lineage (2R WGD) that produced the paralogs Irg1L and Irg1, in which Irg1L is subsequently lost in viviparous mammalian taxa.…”
Section: Discussionmentioning
confidence: 81%
“…However, the two WGD events studied happened around the emergence of vertebrates (~500 million years ago) ( Van de Peer et al 2009), hence they are very ancient events. Here, by analyzing WGD events of different ages, we demonstrate that the findings from Mottes et al (2021) are only true for ancient, but not for recent WGD events. We observed that whether WGD or SSD has a greater contribution to motif formation is tightly linked to the WGD background of the species (i.e., ancient vs recent WGD).…”
Section: (Recent) Whole-genome Duplications Fuel(ed) the Emergence Of...mentioning
confidence: 76%
“…While WGD events are relatively common in plants, such as Arabidopsis, and have also been observed in the yeast Saccharomyces [158,159], identifying WGD pairs or quartets in vertebrates is more difficult. It is by now widely accepted that two rounds of WGD happened at the origin of the vertebrate lineage about 500-550 millions of years ago [160,161] (Figure 2). However, how these global-scale WGD events affected the gene regulatory network is not yet fully understood.…”
Section: • Whole Genome Duplications and Gain In Chromosomesmentioning
confidence: 99%
“…Duplicated genes have stricter requirements for maintaining proper dosage balance [164], are normally involved in signaling, development, and transcriptional regulation and they are represented in gene ontology categories associated with organism's level of complexity [163,165,166]. Therefore, duplicated genes resulting from stabilized WGD tend to be essential, evolutionarily conserved genes, and are related to increased redundancy and complexity, allowing for an advantage under stressful or disturbed environments compared to non-WGD organisms [160,165]. This parallelism between WGD in evolution and the high incidence of WGD in cancer, both strive for increasing fitness to overcome non WGD.…”
Section: • Whole Genome Duplications and Gain In Chromosomesmentioning
confidence: 99%